The Efficient Forecast of Demand Side Management for Flight Simulator Energy Management System - สุขดี, กฤษณะ; วงค์ปัญโญ, วัชระ (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2020)
This study aims to investigate the efficiency of the utilization of renewable energy, which plays a significant role in developing energy assurance and preventing the blackout damage to the Royal Thai Air Force (RTAF) flight simulator facility equivalent to that of the fighter F-22 of U.S. demonstrates. The United State Air National Guard has already applied the research of microgrid and Building Energy Management System (BEMS) to supply energy independently into its flight simulator system. However, this research's dissimilar environments are energy demand, microgrid location, Global Horizon Irradiation (GHI), and weather conditions, which affect the microgrid proficiency performs differently. In addition, ensuring the efficiency of energy-enabled and safe, the key to success for energy planning and management is the Efficiency Forecast of Demand Side Management (DSM) design for isolating the main grid's preliminary problem and increasing the cyber security level of RTAF energy. Consequently, the researcher selects the HOMER Pro® Microgrid Software, which is one of the global commercial microgrid standards for energy modeling tools and other distributed energy projects to simulate the DSM forecast to evaluate the microgrid design in Nanogrid level.